Exploring juror evaluations of expert opinions using the Expert Persuasion Expectancy framework. (6th February 2020) - Martire, Kristy A.; Edmond, Gary; Navarro, Danielle
Abstract : Purpose: Factfinders in trials struggle to differentiate witnesses who offer genuinely expert opinions from those who do not. The Expert Persuasion Expectancy (ExPEx) framework proposes eight attributes logically relevant to this assessment: foundation, field, specialty, ability, opinion, support, consistency, and trustworthiness. We present two experiments examining the effects of these attributes on the persuasiveness of a forensic gait analysis opinion. Methods: Jury‐eligible participants rated the credibility, value, and weight of an expert report that was either generally strong (Exp. 1; N = 437) or generally weak (Exp. 2; N = 435). The quality of ExPEx attributes varied between participants. Allocation to condition (none, foundation, field, specialty, ability, opinion, support, consistency, trustworthiness) determined which attribute in the report would be weak ( cf. strong; Exp. 1), or strong ( cf. weak; Exp. 2). Results: In Experiment 1, the persuasiveness of a strong report was significantly undermined by weak versions of ability, consistency, and trustworthiness. In Experiment 2, a weak report was significantly improved by strong versions of ability and consistency. Unplanned analyses of subjective ratings also identified effects of foundation, field, specialty, and opinion. Conclusions: We found evidence that ability (i.e., personal proficiency), consistency (i.e., endorsement by other experts), and trustworthiness (i.e., objectivity) attributes influence opinion persuasiveness in logically appropriate ways. Ensuring that factfinders have information about these attributes may improve their assessments of expert opinion evidence.